Mail in the Caliphate of Al-Walid bin Abdul-Malik (86-96 AH/705-715 AD) - Alsaeed, Khalid Abdullah (Journal of Humanities & Social Sciences, 2025)
Mail is one of the essential components of any administrative system in any country; through it, it is easy for those in power to know the conditions of their kingdoms and control their situations, in addition to their need for it to communicate with the rulers of other kingdoms. Similar to many contemporary studies that dealt with mail and its conditions in the Islamic eras, the researcher shed light in the first section on the definition of mail, traced the origin of this word, then gave a glimpse of its conditions among some ancient nations, and followed that by referring to the names of postal workers and their jobs, in addition to the animals used in transporting mail, the roads they take, and the stations they stop at. As for the second section, he pointed out that the Arabs in their pre-Islamic era knew mail as indicated by their poetry. The Prophet, peace and blessings be upon him, needed it to monitor the movements of his enemies and to inform the rulers and kings of the call to Islam. The need for it increased during the era of the Rashidun Caliphs to be aware of the conditions of the armies of conquest and to know the news of the subjects in the conquered countries. The mail witnessed a great leap during the era of the Umayyads, as they established a bureau for it, took care of its stations, expanded its work, and increased its means. As for the third section, the researcher devoted it to reviewing the additions made by Caliph Al-Walid bin Abdul-Malik to the postal system, in addition to his contributions to meeting the political, military, security, and even personal needs of the state.